When Literary Men Become Historians: The Role of Literature in Presenting History through Selected Postmodern Fictions- A Thematic Study - Mohammed, Zhino Jabbar (Sulaimani Journal for Humanities, 2019)
This paper is about the role of literature in presenting history in selected postmodern novels. History or retelling past events has become a prominent subject matter of a number of postmodern fictions. This study provides a clearer understanding of the way how literary writers present theme of history through postmodern novels, among them Salman Rushdie’s Shame (1983), Toni Morrison’s Beloved (1987), and Jonathan Safran Foer’s Everything is Illuminated (2002). This paper is significant in the field of Postmodern Literature, in particular, postmodern novels. It will contribute to both fields of postmodernism and history. It will answer the following questions: what is the role of literature in telling history? How does literature make history memorable? Can a literary writer be a historian? How is history presented in the selected postmodern novels? Using the postmodern literary approach, we will reach to the findings of the paper that through the selected postmodern novels, the use of postmodern literary forms and collective memory of the past will affect the reader’s consciousness to make the expressions rather attached to the reader’s senses. Moreover, a literary writer can be a historian as well via entailing a degree of power over people’s perception of actual truth of the past through the use of imagination and rhetorical devices to arouse certain emotions. Also, theme of history has been depicted through the use of literary techniques. The findings of this study would be beneficial and valuable for students and researchers of the literary and cultural studies, departments of English, and British and American Literature especially postmodern novels.
Keywords: Postmodern novels; historiographic metafiction; The Holocaust; trauma; collective memory